The ways and means of ITER: reciprocity and compromise in fusion science diplomacy. (2nd January 2021) - Åberg, Anna
ABSTRACT: ITER (short for International Thermonuclear Experimental Reactor, and the Latin word for 'the way', as in 'the way to new energy'), a controlled thermonuclear fusion experiment currently being built in Cadarache, France, is one of the world's largest technoscientific collaborations. ITER's complex organisation is rooted in decisions taken during the early negotiation phase in the 1990s. This article focuses on this initial period of the ITER negotiations, showing the importance of reciprocity and compromise in the organizational decisions of the project. These decisions were enacted by actors and organisations who strived to keep ITER together through continuous 'backstage' diplomacy work. This work included finding acceptable compromises for the involved Parties on both a diplomatic and scientific level. Looking closely at such work reveals the entangled character of science and diplomacy in large international technoscientific collaborations, as well as the need for compromise to make a project like ITER materialise.